What is the most effective posture to conduct vibration from the lower to the upper extremities during whole-body vibration exercise? - Tsukahara Y; Iwamoto J; Iwashita K; Shinjo T; Azuma K; Matsumoto H (Dove Medical Press, 2016)
Yuka Tsukahara, Jun Iwamoto, Kosui Iwashita, Takuma Shinjo, Koichiro Azuma, Hideo MatsumotoInstitute for Integrated Sports Medicine, Keio University School of Medicine, Tokyo, Japan Background: Whole-body vibration (WBV) exercise is widely used for training and rehabilitation. However, the optimal posture for training both the upper and lower extremities simultaneously remains to be established. Objectives: The objective of this study was to search for an effective posture to conduct vibration from the lower to the upper extremities while performing WBV exercises without any adverse effects. Methods: Twelve healthy volunteers (age: 22–34 years) were enrolled in the study. To measure the magnitude of vibration, four accelerometers were attached to the upper arm, back, thigh, and calf of each subject. Vibrations were produced using a WBV platform (Galileo 900) with an amplitude of 4 mm at two frequencies, 15 and 30 Hz. The following three postures were examined: posture A, standing posture with the knees flexed at 30°; posture B, crouching position with no direct contact between the knees and elbows; and posture C, crouching position with direct contact between the knees and elbows. The ratio of the magnitude of vibration at the thigh, back, and upper arm relative to that at the calf was used as an index of vibration conduction. Results: Posture B was associated with a greater magnitude of vibration to the calf than posture A at 15 Hz, and postures B and C were associated with greater magnitudes of vibration than posture A at 30 Hz. Posture C was associated with a vibration conduction to the upper arm that was 4.62 times and 8.26 times greater than that for posture A at 15 and 30 Hz, respectively. Conclusion: This study revealed that a crouching position on a WBV platform with direct contact between the knees and elbows was effective for conducting vibration from the lower to the upper extremities. Keywords: whole-body vibration exercise, upper extremities, lower extremities